Maternal Transmission of 17q12 Microdeletion: Intrafamilial Phenotypic Variability and Diagnostic Hurdles—A Case Report - Susanna Negrisolo; Gianluca Caridi; Benedetta Antoniello; Elisa Benetti (DNA)
The relatively rare proximal 17q12 microdeletion, including the deletion of the HNF1B gene, is associated with renal cysts and diabetes syndrome (RCAD). This genomic rearrangement results in a wide range of phenotypes, including renal cysts and diabetes, which are consistent with maturity-onset diabetes of the young type 5 (MODY5), Mullerian aplasia/dysgenesis, autism spectrum disorder and schizophrenia, speech delay, learning difficulties, transient neonatal hypercalcemia, and neonatal cholestasis. We describe a girl with a 17q12 microdeletion identified using CGH array analysis (about 1.4 Mb, including HNF1B and LHX1 genes). The same deletion was identified in her mother. The proband had shown cystic and hypodysplastic bilateral kidneys since birth and hypertension, while her mother had bilateral renal cysts and diabetes. Despite suggestive findings in the girl and in the mother, no clinical suspicion arose, and genetic testing was carried out only after referral to a pediatric nephrologist. In children, the identification of 17q12 microdeletion may have a significant impact on the diagnosis, prognosis, and management of renal disease and early-onset type II diabetes. This family with a 17q12 microdeletion confirms intrafamilial phenotypic variability and highlights the importance of including it early on in the analysis of the diagnostic workup of children with renal cystic diseases.